If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -2 + x = 5 + -2 Combine like terms: 7 + -2 = 5 5 + x = 5 + -2 Combine like terms: 5 + -2 = 3 5 + x = 3 Solving 5 + x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + x = 3 + -5 x = 3 + -5 Combine like terms: 3 + -5 = -2 x = -2 Simplifying x = -2
| 6t^2-24t+16=0 | | 13y=4x | | 3x-2+10= | | 3+3*6-2=x | | 0.3(x+40)-0.07(x-20)=8.8 | | -6(m-8)=-2m | | 13y=9x | | X+2x=30(x) | | -3n+7-2n=-13 | | 8x+8+3y=36 | | 5(y+3)-4(1-5y)=-39 | | 17=8x+1-4x | | 4y-4x^3=0 | | 18/-3=6 | | y=x^2+6x+14 | | 4x^2+16x-12y-44=0 | | 51=-3(m+7)+m | | x^2-33x+100=56-9x | | 6x+120=128 | | -18/-3=-6 | | -3(4p+5)-2(5-14p)=3(6+5p) | | 12=5x-7y | | 3xy+12x^2-4yx-10x+7xy-9x^2= | | D+1.0=9.2whatisD | | 9+18=-3(3x-9) | | 0.9x-0.5=6 | | x^2-33x+100=9x+y-56 | | 6x+8=5x+6 | | 9x^2-96x+192=0 | | 3(x+12)-16=8x | | x^2-33+100=9x+y-56 | | 4(3-2x)=3-5x |